Penerapan Sistem Manajemen Kesehatan dan Keselamatan Kerja di Pelabuhan Belawan dan Permasalahan Yang Terjadi - Lisa Anggriani Tanjung; Sri Wahyuni Tanjung; Fadiyah Nurhanasah.S; Nur Fitriani; Shakinah Mawaddah; Yulizar Sukma Rani (Lembaga Pengembangan Kinerja Dosen, 2023)
Based on its astronomical location, Indonesia is located at 6°N – 11°S and 95°East - 141°E, with details namely Belawan port is at point 03° 470 000 LU and 980 420 East. This port is about 24 km from downtown Medan. Accidents at work are things that really need attention and should not be looked down upon. Based on government regulation no. 50 of 2012 which is the result of amendments to the regulation of the Minister of Manpower of the Republic of Indonesia No.Per.05/MEN/1996 concerning implementation of safety management systems and occupational health (SMK3) is part of the overall system includes organizational structure, planning, responsibility, implementation, process, procedures, maintenance of occupational safety and health policies in order risk control related to work activities in order to create a place Safe, efficient and productive work. The formulation of the problem in this study namely application of SMK3 at Belawan Port and the problems that occur. With research objectives to describe the safety management system and occupational health on the Pertamina Belawan ship, to find out the safety system work at Belawan port and find out how far the system has been implemented occupational safety and health management implemented at the port Belawan.